Oral irritation in patients with chemosensory dysfunction. (20th April 2021) - Han, Pengfei; Seo, Han‐Seok; Klockow, Marie; Yan, Xiaoguang; Hähner, Antje; Hummel, Thomas
Abstract: Introduction: Evidence accumulates to support the interaction among gustatory, olfactory and trigeminal sensations. While olfactory dysfunction is associated with impaired taste or intranasal trigeminal perception, less is known about the perception of oral irritative intensity among patients with olfactory or gustatory dysfunctions. Method: 148 patients with olfactory and/or gustatory dysfunctions received oral administration of chili powder samples with varied irritation levels, and rated the oral irritation intensity on an 11‐point scale. Gustatory sensitivity was assessed using the 'Taste Strips' test among a subset of the patients (N = 25). Other variables including the aetiology of disease and a frequency of spicy food consumption were also recorded for exploratory analyses. Results: Participants with anosmia rated oral irritations of chili powder significantly less than participants with normosmia. In the subsample, a positive correlation was observed between the individual scores of the 'Taste Strips' test and ratings of oral irritation intensity at the highest level of chili powder test. There were no effects of age, aetiology, subjective ratings of sensitivity to spicy food or frequency of spicy food consumption with respect to oral irritation intensity of chili powder samples. Conclusion: The current results showed reduced oral irritation intensity among patients with severe olfactory loss. Impaired oral irritative perception among these participants may be related to disturbed central nervous interactions between the various sensory systems involved in flavour perception. Abstract : Patients with severe olfactory dysfunctions have reduced oral irritation intensity. Impaired oral irritative perception among these participants may be related to disturbed central nervous interactions between the various sensory systems involved in flavour perception.